"Developing Students’ Financial Literacy Skills Through An Integrated Approach In Mathematics Education" (Journal of Pedagogical Inventions and Practices, 2026)
This article analyzes the issue of developing students' financial literacy skills through an integrated approach in the process of teaching mathematics. In response to the increasing demands of global economic processes and the growing need for financial awareness in society, promoting financial literacy in general education schools has become a pressing objective. This study presents a methodology for integrating financial concepts through real-life mathematics topics—such as interest, credit, budgeting, graphical analysis, and statistical data. Modern pedagogical technologies like project-based learning, problem-based learning, and game-based learning were employed in the instructional process. Experimental research demonstrated that students' financial literacy levels increased, and their motivation toward mathematics improved. This approach fostered students' critical thinking, decision-making, and budgeting skills. The study concludes with recommendations for developing mathematics education as a tool for enhancing financial culture